2015
DOI: 10.1007/s00384-015-2322-7
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hyperglycemia and adverse outcomes in patients undergoing colorectal surgery: results from the Michigan surgical quality collaborative database

Abstract: Following colorectal operations, superficial SSI, sepsis, and death are associated with postoperative serum hyperglycemia in patients without diabetes, but not those with diabetes. Vigilant postoperative BG monitoring is critical for all patients undergoing colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
2
28
1
2
Order By: Relevance
“…Other authors, using The Michigan Surgical Quality Collaborative database, assessed the relationship between high blood glucose levels in the early postoperative period after colorectal operations and found that superficial surgical site infections, sepsis, and death were associated with postoperative serum hyperglycemia in patients without diabetes and concluded that glucose monitoring is critical for all patients undergoing colorectal surgery. 17 In addition, clinical outcomes associated with postoperative hyperglycemia in cardiac surgery patients who were stratified by diabetes status demonstrated that in patients without diabetes, hyperglycemia ($180 mg/dL) was associated with an increase in infections and respiratory complications. 18 A systematic review of the effects of tight glycemic control (blood glucose levels #200 mg/ dL) reported a reduction in the incidence of surgical site infections in adult patients with diabetes after cardiac surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors, using The Michigan Surgical Quality Collaborative database, assessed the relationship between high blood glucose levels in the early postoperative period after colorectal operations and found that superficial surgical site infections, sepsis, and death were associated with postoperative serum hyperglycemia in patients without diabetes and concluded that glucose monitoring is critical for all patients undergoing colorectal surgery. 17 In addition, clinical outcomes associated with postoperative hyperglycemia in cardiac surgery patients who were stratified by diabetes status demonstrated that in patients without diabetes, hyperglycemia ($180 mg/dL) was associated with an increase in infections and respiratory complications. 18 A systematic review of the effects of tight glycemic control (blood glucose levels #200 mg/ dL) reported a reduction in the incidence of surgical site infections in adult patients with diabetes after cardiac surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Изучение влияния гипергликемии на клиниче-ские исходы у пациентов хирургического профиля с СД или без него привлекает все больше исследовате-лей [35][36][37]. Длительное время послеоперационная СГ рассматривалась как адаптационная реакция на стресс, и ее коррекции не уделяли большого внимания.…”
Section: инсулинорезистентность и стрессовая гипергликемияunclassified
“…при изучении уровня гликемии и риска инфекционных осложнений в колоректаль-ной хирургии у 5145 пациентов, среди которых 1072 имели СД, отметили, что повышение гликемии более 10 ммоль/л у пациентов без СД сопровождалось повы-шением риска развития нагноения послеоперационной раны (OR (odds ratio) 1,53; p=0,03), сепсиса (OR 1,61; p<0,01) и летальности (OR 2,26; p<0,01), в отличие от па-циентов с СД, у которых значимой взаимосвязи между гипергликемией и инфекционными осложнениями по-лучено не было [37].…”
Section: инсулинорезистентность и стрессовая гипергликемияunclassified
“…1 Van den Berghe et al showed a 30% decrease in mortality of critically ill patients, whose glucose levels were kept within strict margins to prevent hyperglycemia. 5 Moreover, perioperative hyperglycemia is known to correlate with a variety of complications such as postoperative infections, [6][7][8][9][10] increased delirium rates, 11 renal failure 12 and impaired immune function. 13 In addition, hyperglycemia negatively affects the human brain.…”
Section: Introductionmentioning
confidence: 99%